2001
DOI: 10.1007/s001050051340
|View full text |Cite
|
Sign up to set email alerts
|

Arzneimittelreaktion auf Terbinafin unter dem Bild einer akuten generalisierten exanthematischen Pustulose (AGEP)

Abstract: Oral terbinafine (Lamisil) is a widely used and effective therapy of dermatophyte infections. A 20-year-old patient was treated with oral terbinafine for an inguinal-scrotal fungal infection and developed an acute generalized exanthematic pustulosis (AGEP) and fever. Histological examination of skin biopsy revealed subcorneal and spongiform pustules. The diagnosis of an AGEP induced by terbinafine was established based on the history, clinical manifestations, and laboratory findings. Clinical features, differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The sensitivity of patch testing to drugs in AGEP has been reported to be approximately 50% [12, 13]. Previous reports have indicated that the LTT may be helpful in determining drug allergy in AGEP despite negative skin testing [14,15,16,17]. To our knowledge a significant lymphocyte stimulation to corticosteroids has not been reported previously in AGEP.…”
Section: Discussionmentioning
confidence: 53%
“…The sensitivity of patch testing to drugs in AGEP has been reported to be approximately 50% [12, 13]. Previous reports have indicated that the LTT may be helpful in determining drug allergy in AGEP despite negative skin testing [14,15,16,17]. To our knowledge a significant lymphocyte stimulation to corticosteroids has not been reported previously in AGEP.…”
Section: Discussionmentioning
confidence: 53%
“…Sideroff et al (2) stated that the course of AGEP is self-limiting with the pustulosis tending to resolve within 15 days. Steroid use was associated with those cases where the drug eruption was prolonged and tended to last for longer that the stated 15 days (Table II) (4,(6)(7)(8)(9)(10)(11). Given this prolonged temporal association and the fact that our patient developed AGEP despite concurrent oral corticosteroids, we question the therapeutic value of glucocorticoids, in the management of AGEP.…”
Section: Case Reportmentioning
confidence: 71%
“…In 9 out of 13 reported cases oral corticosteroids were used for the treatment of AGEP (4)(5)(6)(7)(8)(9)(10)(11)(12). The phenomenon of severe cutaneous adverse drug reactions developing in patients receiving corticosteroids for the treatment of chronic diseases has been described before.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign side effects are observed in about 10% of patients, usually affecting the digestive tract and the skin (ageusia, nausea, diarrhea, erythema, pruritus, urticaria), occurring in 4.9 and 2.3% of patients, respectively [19, 20]. In rare cases, there have been reports of hepatitis, severe hematological abnormalities, and serious cutaneous side effects have been reported, such as bullous pemphigoid [21], acute generalized exanthematous pustulosis [22,23,24], toxic epidermal necrolysis [25, 26], hypersensitivity reaction (‘DRESS syndrome’) [27], erythema multiforme [26, 28], pustular psoriasis [29] or SCLE [11,12,13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%